Drosophila melanogaster as a neurobehavioral model for sex differences in stress response - Tawa, Elisabeth; Notterman, Daniel (Frontiers in Behavioral Neuroscience, 2025)
Sex differences are observed in several neurologic and psychiatric disorders. Many aberrant behavioral symptoms can be characterized clinically as either internalizing or externalizing, which tend to manifest disproportionately in females or males, respectively. Stress may precipitate or amplify these behavioral disturbances, which often start in childhood and adolescence but persist into adulthood. Increased understanding of sex differences in stress-induced behavioral changes and their underlying molecular mechanisms is integral to developing better therapeutics specifically tailored to males and females. Here, we highlight the potential of Drosophila melanogaster (D. melanogaster) as a model for the neurobiological study of sex differences in stress-altered behavior. We first review paradigms for stressing D. melanogaster, with an emphasis on social environmental stress. We then introduce behavioral tests that can be used to quantify stress-induced behaviors in flies and note sex differences that emerge in response to stress. Finally, we provide an overview of the known molecular and cellular mechanisms underlying stress-induced behavioral change, with a focus on sex differences and studies incorporating social isolation or crowding.